A taxonomic revision of Anisophyllea (Anisophylleaceae) from Madagascar - Chen, Xin; He, Hai; Zhang, Libing (Phytotaxa, 2013)
A taxonomic revision of Anisophyllea (Anisophylleaceae) from Madagascar was carried out. Five species of the genus are recognized, of which four are described as new. The five species include Anisophyllea fallax, A. madagascarensis sp. nov., A. masoalensis sp. nov., A. parafallax sp. nov., and A. schatzii sp. nov. A key to the Malagasy species of Anisophyllea is provided. All species are described and illustrated. Information on their distribution and habitat is given. Taxonomic issues are discussed. The IUCN Red List categories are assessed.